Odpowiedź :
zad1.
3*((-2) + y) + 2*(y-(-2)) = 3*(y-2) + 2*(y+2) = 3y - 6 + 2y + 4 = 5y -2
zad2.
4*((-2) - y) - (5+(-2))*(y+1) = 4*(-2 - y) - 3(y+1) = -8 - 4y - 3y - 3 = -7y - 11
3*((-2) + y) + 2*(y-(-2)) = 3*(y-2) + 2*(y+2) = 3y - 6 + 2y + 4 = 5y -2
zad2.
4*((-2) - y) - (5+(-2))*(y+1) = 4*(-2 - y) - 3(y+1) = -8 - 4y - 3y - 3 = -7y - 11
Odpowiedź:
3 ( x + y ) + 2 ( y – x ) =
3( ( - 2)+y) +2(y - ( - 2))= - 6+3y+2y+4= 5y - 2
4 ( x – y ) - ( 5 + x ) ( y + 1 ) =
4(( - 2) -y) - (5+ ( - 2))(y+1)= - 8 - 4y - (5 - 2)(y+1)= - 8 - 4y - 3(y+1)= - 8 -4y - 3y - 3=
- 7y - 11
Szczegółowe wyjaśnienie: